Aesthetical entanglements in mathematics education - Nemirovsky, Ricardo; Kathotia, Vinay; Mégrourèche, Charlotte (Frontiers in Education, 2023)
In this paper we develop a perspective on the diverse aesthetics historically associated with mathematics, inspired by Rancière's approach to aesthetics and politics. We call 'Silencing Aesthetics' a dominant aesthetic that Rota has characterised as a "copout (...) intended to keep our formal description of mathematics as close as possible to the description of a mechanism." The challenge this paper attempts to explore is how to question silencing aesthetics to make space for inclusive ones. Our efforts have focused on setting up and studying inclusive and pluralist 'Studios', gathering craftworkers, anthropologists, mathematics educators and mathematics enthusiasts. We include here a case study based on a conversation among basket weavers, anthropologists, and mathematics educators, focused on the artisanal and mathematical nature of knots. We discuss the implications of aesthetical entanglements, such as those in our case study, for mathematics learning.